Lack of COL6/collagen VI causes megakaryocyte dysfunction by impairing autophagy and inducing apoptosis. Issue 3 (4th March 2023) - Abbonante, Vittorio; Malara, Alessandro; Chrisam, Martina; Metti, Samuele; Soprano, Paolo; Semplicini, Claudio; Bello, Luca; Bozzi, Valeria; Battiston, Monica; Pecci, Alessandro; Pegoraro, Elena; De Marco, Luigi; et al.
ABSTRACT: Endoplasmic reticulum stress is an emerging significant player in the molecular pathology of connective tissue disorders. In response to endoplasmic reticulum stress, cells can upregulate macroautophagy/autophagy, a fundamental cellular homeostatic process used by cells to degrade and recycle proteins or remove damaged organelles. In these scenarios, autophagy activation can support cell survival. Here we demonstrated by in vitro and in vivo approaches that megakaryocytes derived from col6a1 −⁄− (collagen, type VI, alpha 1) null mice display increased intracellular retention of COL6 polypeptides, endoplasmic reticulum stress and apoptosis. The unfolded protein response is activated in col6a1 −⁄− megakaryocytes, as evidenced by the upregulation of molecular chaperones, by the increased splicing of Xbp1 mRNA and by the higher level of the pro-apoptotic regulator DDIT3/CHOP. Despite the endoplasmic reticulum stress, basal autophagy is impaired in col6a1 −⁄− megakaryocytes, which show lower BECN1 levels and reduced autophagosome maturation. Starvation and rapamycin treatment rescue the autophagic flux in col6a1 −⁄− megakaryocytes, leading to a decrease in intracellular COL6 polypeptide retention, endoplasmic reticulum stress and apoptosis. Furthermore, megakaryocytes cultured from peripheral blood hematopoietic progenitors of patients affected by Bethlem myopathy and Ullrich congenital muscular dystrophy, two COL6-related disorders, displayed increased apoptosis, endoplasmic reticulum stress and impaired autophagy. These data demonstrate that genetic disorders of collagens, endoplasmic reticulum stress and autophagy regulation in megakaryocytes may be interrelated. Abbreviations: 7-AAD: 7-amino-actinomycin D; ATF: activating transcriptional factor; BAX: BCL2 associated X protein; BCL2: B cell leukemia/lymphoma 2; BCL2L1/Bcl-xL: BCL2-like 1; BM: bone marrow; COL6: collagen, type VI; col6a1 −⁄− : mice that are null for Col6a1 ; DDIT3/CHOP/GADD153: DNA-damage inducible transcript 3; EGFP: enhanced green fluorescent protein; ER: endoplasmic reticulum; reticulophagy: endoplasmic reticulum-selective autophagy; HSPA5/Bip: heat shock protein 5; HSP90B1/GRP94: heat shock protein 90, beta (Grp94), member 1; LAMP2: lysosomal associated membrane protein 2; MAP1LC3B/LC3B: microtubule-associated protein 1 light chain 3 beta; Mk: megakaryocytes; MTOR: mechanistic target of rapamycin kinase; NIMV: noninvasive mechanical ventilation; PI3K: phosphoinositide 3-kinase; PPP1R15A/GADD34: protein phosphatase 1, regulatory subunit 15A; RT-qPCR: reverse transcription-quantitative real-time PCR; ROS: reactive oxygen species; SERPINH1/HSP47: serine (or cysteine) peptidase inhibitor, clade H, member 1; sh-RNA: short hairpin RNA; SOCE: store operated calcium entry; UCMD: Ullrich congenital muscular dystrophy; UPR: unfolded protein response; WIPI2: WD repeat domain, phosphoinositide-interacting 2; WT: wild type; XBP1: X-box binding protein 1.